Impact of body mass index on postoperative complications and long‐term survival in patients with esophageal squamous cell cancer. Issue 3 (19th March 2015) - Kamachi, K.; Ozawa, S.; Hayashi, T.; Kazuno, A.; Ito, E.; Makuuchi, H.
Summary: Undernutrition and cachexia have been suggested to be risk factors for postoperative complications and survival in cancer patients. The aim of this study was to investigate whether body mass index (BMI) is related to the short‐term and long‐term outcomes in patients who undergo an esophagectomy for the resection of esophageal squamous cell cancer (ESCC). Three hundred forty patients who underwent an esophagectomy for the resection of ESCC between 2003 and 2008 were retrospectively reviewed. The patients were divided into two groups: an L‐BMI group characterized by a BMI < 18.5 kg/m 2 and an N‐BMI group characterized by a BMI ≥ 18.5 kg/m 2 . Clinical and pathological outcome were compared between groups. The study included 40 patients in the L‐BMI group and 300 patients in the N‐BMI group. A clinicopathological assessment showed that nodal involvement was seen more frequently in the L‐BMI group ( P = 0.016). Pulmonary complications seemed to occur more frequently in the L‐BMI group ( P = 0.006). The 5‐year overall survival rate was higher in the N‐BMI group (63.6%) than in the L‐BMI group (32.3%) ( P < 0.001). The 5‐year disease‐free survival rate was also higher in the N‐BMI group (58.0%) than in the L‐BMI group (33.6%) ( P = 0.001). In multivariate analysis, the BMI (hazard ratio, 2.154; 95% CI, 1.349–3.440, P = 0.001) was found to be an independent prognostic factor for overall survival. Our data suggested that a lower BMI not only increased pulmonary complications but also impaired overall and disease‐free survival after an esophagectomy for the resection of ESCC.